Bump, set, spike: Using analytics to rate volleyball teams and players - Bagley, C.; Ware, B. (Sloan Sports Conference, March 3-4, 2017, Hynes Convention Center, 2017)
This paper seeks to outline and quantify methods to objectively rate six fundamental skills in volleyball: i) serve,ii) reception, iii) set, iv) attack, v) block, and vi) dig.While these skills are currently rated in competitive volleyball, there is no method currently in place that will consistently and objectively rate players and teams. With the ability to consistently grade these fundamentals across a large amount of data, it becomes possible to accurately predict matchups and determine player and team success.